2021
DOI: 10.1080/22221751.2021.1988725
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and pathogenic investigations of Streptococcus suis serotype 7 population derived from a human patient and pigs

Abstract: Streptococcus suis is one of the important emerging zoonotic pathogens. Serotype 2 is most prevalent in patients worldwide. In the present study, we first isolated one S. suis serotype 7 strain GX69 from the blood culture of a patient with septicemia complicated with pneumonia in China. In order to deepen the understanding of S. suis serotype 7 population characteristics, we investigated the phylogenetic structure, genomic features, and virulence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 55 publications
2
37
0
Order By: Relevance
“…Although we cannot gain these strains to perform animal infection experiments due to their NCBI source, their pathogenicity deserves attention. In addition, the pathogenic potential of S. suis varies by serotypes and MLST: in serotype 2 strains, ST1 was the most associated with disease in both pigs and humans in Europe, Asia, Africa and South America, and ST7 (a single locus variant of ST1) was only endemic to China, which was responsible for human outbreaks in 1998 and 2005 in this country (Segura et al., 2020); in serotype 9 strains, ST16 included one isolate from a human patient and one from a diseased pig, harbouring more virulence genes (Willemse et al., 2019); in serotype 7 strains, ST373 presented a higher zoonotic potential (Liang et al., 2021). In this study, three serotype 8 representative strains belonging to ST1241 were selected, and all of them were defined as virulent strains in the zebrafish and mice infection experiments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although we cannot gain these strains to perform animal infection experiments due to their NCBI source, their pathogenicity deserves attention. In addition, the pathogenic potential of S. suis varies by serotypes and MLST: in serotype 2 strains, ST1 was the most associated with disease in both pigs and humans in Europe, Asia, Africa and South America, and ST7 (a single locus variant of ST1) was only endemic to China, which was responsible for human outbreaks in 1998 and 2005 in this country (Segura et al., 2020); in serotype 9 strains, ST16 included one isolate from a human patient and one from a diseased pig, harbouring more virulence genes (Willemse et al., 2019); in serotype 7 strains, ST373 presented a higher zoonotic potential (Liang et al., 2021). In this study, three serotype 8 representative strains belonging to ST1241 were selected, and all of them were defined as virulent strains in the zebrafish and mice infection experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Genes mrp , sly and epf were not virulence indicators for serotype 7 strains. Instead, their distribution was linked to serotype 7 evolution (Liang et al., 2021). We did not observe the correlation between the genotype of putative virulence‐associated genes and the virulence phenotype in serotype 8 strains.…”
Section: Discussionmentioning
confidence: 99%
“…Liang et al . reported that four representative strains of S. suis serotype 7 isolated from healthy pig tonsils were identified as virulent strains; two of them belonged to ST373, the same sequence type with serotype 7 human isolate GX69, suggesting we should be aware of the public health threat posed by S. suis serotype 7 ST373 strains [ 13 ]. Wang et al .…”
Section: Introductionmentioning
confidence: 99%
“…Among the 29 described serotypes of S. suis , serotype 2 is the most common cause of human infections ( Goyette-Desjardins et al, 2014 ; Okura et al, 2016 ). However, human cases have also been reported due to the rare serotypes 4, 5, 7, 9, 14, 16, 21, 24, and 31 ( Nghia et al, 2008 ; Callejo et al, 2014 ; Goyette-Desjardins et al, 2014 ; Hatrongjit et al, 2015 ; Kerdsin et al, 2017 ; Liang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Among 29 serotypes, WGS has been applied to the serotype 2 strains worldwide for, as examples, characterization of outbreaks, evaluation of S. suis reinfection, determining the population structure of S. suis strains, and identifying pathotypes or virulence traits ( Estrada et al, 2019 ; Hatrongjit et al, 2020 ). Several studies have also been conducted on serotypes other than serotype 2 including serotypes 3–9, 14, 16, 19, 20, 21, 22, 26, and unencapsulated strains, although most of them were of swine origin ( Hu et al, 2011 ; Wang et al, 2013a , b , 2014 ; Baig et al, 2015 ; Yoshida et al, 2017 ; Zheng et al, 2018 ; Niemann et al, 2019 ; Stevens et al, 2019 ; Bunk et al, 2021 ; Liang et al, 2021 ; Nicholson et al, 2021 ). To date, there has been no WGS performed on S. suis serotype 24 strains recovered from humans.…”
Section: Introductionmentioning
confidence: 99%